'Writing' children's literate identities: the meaning of language in multilingual, multicultural contexts*. (2nd April 2016) - Yoon, Haeny S.
Abstract : Writing is used for various purposes: to accomplish political agendas, build relationships, assert identities, positioning texts as meaningful beyond printed letters on a page. Therefore, teaching children to write is a cultural practice, an invitation to enter into a larger community where identities are created, practiced, and re-imagined using texts. In following this, it is important to study the teaching of writing in schools, as arguably, many children learn to write in narrow ways in classrooms. In this paper, I examine how written language is presented to and understood by children in classrooms – a space where the potential of written texts is often diminished and narrowed. Drawing from a semester-long case study in two kindergarten classrooms, I explore how writing is taken up and embodied by young children. I argue for a reconceptualization of how language arts are taught to young children, especially in an increasingly standardized system.